In vitro antibacterial activity of photoactivated flavonoid glycosides against Acinetobacter baumannii - Maryam Pourhajibagher; Zahra Javanmard; Abbas Bahador (AMB Express)
Abstract Acinetobacter baumannii’s extensive antibiotic resistance makes its infections difficult to treat, so effective strategies to fight this bacterium are urgently needed. This study aims to evaluate the effectiveness of antimicrobial photodynamic therapy (aPDT) mediated by Rutin-Gal(III) complex and Quercetin against A. baumannii. Absorbance spectra, fluorescence spectra, and minimum inhibitory concentration (MIC) of Rutin-Gal(III) complex and Quercetin were determined. The intracellular reactive oxygen species (ROS), extracellular polymeric substances (EPS), cell membrane permeability, expression of ompA and bla OXA−23, anti-biofilm activity, and anti-metabolic activity of Rutin-Gal(III) complex- and Quercetin-mediated aPDT were measured. Rutin-Gal(III) complex and Quercetin revealed absorption peaks in the visible spectra. Quercetin and Rutin-Gal(III) complex displayed fluorescence peaks at 524 nm and 540 nm, respectively. MIC values for the Rutin-Gal(III) complex and Quercetin were 64 µg/mL and 256 µg/mL, respectively. Quercetin- and Rutin-Gal(III) complex-mediated aPDT significantly reduced the colony forming units/mL (58.4% and 67.5%), EPS synthesis (47.4% and 56.5%), metabolic activity (30.5% and 36.3%), ompA (5.5- and 10.5-fold), and bla OXA−23 (4.1-fold and 7.8-fold) genes expression (respectively; all P < 0.05). Quercetin- and Rutin-Gal(III) complex-mediated aPDT enhanced notable biofilm degradation (36.2% and 40.6%), ROS production (2.55- and 2.90-folds), and membrane permeability (10.8– and 9.6-folds) (respectively; all P < 0.05). The findings indicate that Rutin-Gal(III) complex- and Quercetin-mediated aPDT exhibits antibacterial properties and could serve as a valuable adjunctive strategy to conventional antibiotic treatments for A. baumannii infections. One limitation of this study is that it was conducted solely on the standard strain; testing on clinical isolates would allow for more reliable interpretation of the results.